Geographic Variation of Phyllodiaptomus tunguidus Mitogenomes: Genetic Differentiation and Phylogeny - Zhang, Xiao-Li; Liu, Ping; Xu, Shao-Lin; Rizo, Eric Zeus; Zhang, Qun; Dumont, Henri J.; Han, Bo-Ping (Frontiers in Genetics, 2021)
Phyllodiaptomus tunguidus (Copepoda: Calanoida) is largely endemic to and widespread in freshwater in southern China, where it inhabits a complex landscape from lowland to highland across an elevation gradient of 2000 m. A deep genetic differentiation can be expected between its most distant geographic populations. Here, we sequenced nine mitogenomes from diverse populations. All mitogenomes contained 37 genes, including 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and one control region. Their base composition, genetic distance and tRNA structure indeed revealed a wide differentiation between mitogenomes. Two P. tunguidus from Guangxi near Vietnam differed from the other seven by up to 10.1%. Their tRNA-Arg had a complete clover-leaf structure, whereas that of the others did not contain an entire dihydrouridine arm. The nine mitogenomes also differed in the length of rRNA. NJ, ML and Bayesian analyses all split them into two clades, viz. the two P. tunguidus from Guangxi (Clade 1), and the other seven (Clade 2). Both the structure and phylogeny of the mitogenomes suggest that P. tunguidus has complex geographic origin, and its populations in Clade 1 have long lived in isolation from those in Clade 2. They currently reach the level of subspecies or cryptic species. An extensive phylogenetic analysis of Copepoda further verified that Diaptomidae is the most recently diverging family in Calanoida and that P. tunguidus is at the evolutionary apex of the family.